POLA PIKIR ANAK USIA DINI PENGGUNA TIKTOK PADA ERA 5.0 DI KOTA PALEMBANG - Melinda Puspita Sari Jaya; Maspupah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to uncover the mindset of young children who actively use the social media platform TikTok in the context of the Society 5.0 era in Palembang City. The study uses a qualitative approach with a phenomenological method to gain an in-depth understanding of the subjective experiences of children aged 4–6 years in accessing and using TikTok. Data was collected through interviews, observations, and documentation of five children residing in Kelurahan 12 Ulu, Kecamatan Seberang Ulu II, Palembang City. The data analysis technique used in this study is the interactive model by Miles, Huberman, and Saldana, which includes three stages: data reduction, data presentation, and drawing conclusions. To ensure data validity, triangulation techniques were used, including source triangulation, method triangulation, and theory triangulation. This was done to ensure that the data obtained was truly reliable and reflected the reality on the ground. The research findings indicate that TikTok has an impact on the cognitive development of young children in the form of concrete, creative, and imaginative thinking patterns. Children show a tendency to imitate content, develop self-expression, and use language and movements that are popular on TikTok. Some children also show an increase in self-confidence and social skills. However, there are also negative impacts such as attachment to gadgets, the use of slang that is not age-appropriate, and the inability to distinguish between factual and entertainment content. The role of parents is crucial in guiding children to use TikTok in a positive manner. This study contributes to understanding the influence of social media on children's cognitive development and emphasizes the importance of control and education in the use of digital technology among young children.